The influence of neighbouring species on ecological variation of the selected subpopulations of Iris sibirica L. - Kostrakiewicz-Gierałt, Kinga (Biodiversity: Research and Conservation, 2015)
This study results show that the I. sibirica subpopulations occurring in the site dominated by small meadow species and macroforbs were in unsatisfactory condition, those inhabiting the sites dominated by large-tussock grasses and shrubs were in a quite good condition, while the subpopulation inhabiting the plot overgrown by shrubs and trees showed the worst condition